The Effect of Prolonged Duration of Intensity Modulated Radiotherapy for Nasopharyngeal Carcinoma - Hua, Yi-Jun; Ou-Yang, Yan-Feng; Zou, Xiong; Xia, Le; Luo, Dong-Hua; Chen, Ming-Yuan (Frontiers in Oncology, 2021)
Abstract Purpose: Radiotherapy is the most important primary treatment for patients with nasopharyngeal carcinoma. Generally, the treatment duration of radiotherapy takes six or six and half weeks with 30 to 33 fractions. The current study was conducted to evaluate the association between prognosis and the duration of radiotherapy in nasopharyngeal carcinoma patients. Methods: Patients with primary nasopharyngeal carcinoma who were treated with intensity-modulated radiotherapy and concurrent cisplatin-based chemotherapy, with or without induction chemotherapy between January, 2008 and December, 2013 at a single institution were retrospectively reviewed. Results: In total, 1292 patients were included. At a median follow-up of 71.0 months (range 2.0–126.0 months), locoregional recurrence, distant failure and death were observed in 8.8%, 12.2% and 15.6% of all patients, respectively. Estimated 5-year locoregional relapse–free survival, distant metastasis–free survival, progression-free survival and overall survival in patients with radiation ≤ 7 weeks versus patients with radiation ＞7 weeks were: 93.2% versus 87.0% (P＜0.001), 89.4% versus 84.4% (P = 0.016), 79.8% versus 70.6% (P ＜0.001) and 87.2% versus 78.4% (P＜0.001), respectively. Conclusions: Prolonged duration of radiotherapy with a significantly higher risk of distant metastasis and death in nasopharyngeal carcinoma patients. Understanding this point, healthcare providers should make efforts to avoid prolonged duration of radiotherapy to minimize the risk of treatment failure.